Implementation of a Web-Based Outgoing Letter Application to Enhance Administrative Efficiency in Pertumbukan Village, Wampu District - Yusman, Yanti; Rian Putra, Randi; Sinaga, Intan (Cattleya Darmaya Fortuna, 2024)
This study explores the implementation of a web-based outgoing letter application designed to improve administrative efficiency in Pertumbuhan Village, Wampu District. With the increasing demands for efficient governance and public service delivery, the adoption of digital tools has become essential. The research evaluates the application's impact on reducing processing time, minimizing errors, and improving overall communication within the village administration.